Application of Multi-Source Remote Sensing Technology in Smart Transportation - He, Siyi; Jiang, Kuiliang; Li, Jinghui (Transactions on Environment, Energy and Earth Sciences, 2024)
Under the background of deepening urbanization, the rapid growth of traffic flow poses a great challenge to the traffic monitoring system. However, the development of intelligent transportation systems (ITS) integrates advanced information technology and multiple remote sensing technologies, thus opening up a new path for efficient urban traffic management. This study explores in depth the applications of unmanned aerial vehicle remote sensing technology, LiDAR technology, and airborne remote sensing technology in autonomous driving technology, traffic flow monitoring, road condition assessment, and vehicle environment perception. This paper analyzes that UAV remote sensing technology can provide a wide field of vision and accurate environmental awareness for autonomous vehicles by carrying high-resolution cameras and sophisticated radar devices, so as to enhance the response ability of autonomous vehicle to complex traffic scenes. This article also analyzes the application of LiDAR technology in achieving precise vehicle positioning and navigation, as well as road information collection. This technology utilizes laser pulses to generate high-precision 3D point cloud maps, providing accurate distance measurement and environmental modeling for autonomous vehicles. The airborne remote sensing technology can be applied in road condition assessment, accident detection and response, environmental monitoring, and traffic congestion analysis due to its high-resolution monitoring capability, wide coverage, and fast response characteristics. Multi-source remote sensing technology plays a vital role in improving the efficiency of traffic monitoring, optimizing traffic flow management, and promoting the advancement of autonomous driving technology.